Effectiveness of Ethnomathematics Learning with Taekwondo Basic Techniques in Understanding the Concept of Geometry for Junior High School Students - Ayu Septia Ningrum; Moh. Zayyadi; Fetty Nuritasari; Sri Indriati Hasanah (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
The understanding of geometry concepts among junior high school students remains relatively low due to the abstract and teacher-centered nature of mathematics learning, which emphasizes formula memorization rather than meaningful conceptual understanding, making it difficult for students to connect geometry concepts with real-life contexts; therefore, an innovative and contextual learning approach, such as ethnomathematics-based learning, is needed. This study presents a novel approach by integrating ethnomathematics with basic taekwondo techniques through a systematic mapping of geometric concepts into structured taekwondo movement patterns, where kicking and stance positions represent angle types and measures, body turns illustrate rotational transformations, balanced stances demonstrate symmetry, and sequential movement patterns model basic geometric transformations. This research was conducted to evaluate the impact of integrating ethnomathematics instruction with fundamental taekwondo techniques on the understanding of geometric concepts among seventh graders at SMP Negeri 7 Pamekasan. The study utilized a quantitative approach with an experimental methodology featuring 40 students, who were split into two groups: an experimental class (VIIA) and a control class (VIIB), with each consisting of 20 students. Data collection involved pretests and posttests through written assessments and a validated questionnaire for student responses. The analysis of the data was executed using descriptive statistics, the N-Gain test, a homogeneity test, and a t-test. Findings revealed that the implementation of ethnomathematics education grounded in basic taekwondo techniques was significantly more effective in enhancing students’ comprehension of geometric concepts compared to traditional teaching methods.